(untitled) (Ameghiniana, 2014)
Leaves of Ocotea sp. (Lauraceae), are identified and described. They were found in argilIaceous beds of Paraná Formation in Villa Urquiza, Entre Rios Province, Argentina. The affinities and palaeobiogeographical relations are discussed.